Implementation Of Citizenship Education As A Model For Student Character Development In Elementary Schools - Ariany, Farida; Aminullah, Aminullah; Garnika, Eneng (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Character education is the main foundation in building a generation of integrity in Indonesia. Through character education, students are not only given an understanding of moral values such as piety, faith, honesty, caring, and ethics, but also guided to embody them in daily behavior in accordance with the values of Pancasila. The subject of Civic Education (PKn) is a strategic vehicle in transforming character values to students, with the aim of forming democratic citizens with strong character. The implementation of character education through the subject of PKn in elementary schools has been carried out with careful planning by teachers, including the selection of character values to be developed and the integration of values in the introductory, core, and closing activities of learning. Assessment of the implementation of character education is carried out through three domains, namely cognitive, affective, and psychomotor, to ensure the success of character internalization in students. Amid the challenges of the era of globalization that erode morality, this study aims to analyze the implementation of civic education in shaping honest and responsible character in elementary school students. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research results revealed that the success of the implementation of civic education is determined by the integration of three main aspects: planning, implementation, and evaluation, which involve the principal, civics teachers, and students in ongoing synergy.